ฤทธิ์ต้านเอนไซม์อะเซทิลโคลินเอสเตอเรสและต้านอนุมูลอิสระ ของสมุนไพรไทยบางชนิดในวงศ์ Asteraceae และ Cucurbitaceae - หลังยาหน่าย สุพัตร์; จันทร์เอียด ประภาพร; ภูริพัฒนาวงษ์ จินดาพร (Science Essence Journal, 2017)
บทคัดย่อ อัลไซเมอร์เป็นโรคทางระบบประสาทที่พบมากที่สุดในกลุ่มอาการสมองเสื่อม ซึ่งมีแนวโน้มเพิ่มมากขึ้นในผู้สูงอายุ วิธีหนึ่งสำหรับการรักษาโรคอัลไซเมอร์ในปัจจุบันคือการเพิ่มระดับสารสื่อประสาทอะเซทิลโคลีนในสมองโดยการใช้ยาในกลุ่มยับยั้งการทำงานของเอนไซม์อะเซทิลโคลีนเอสเตอเรส ดังนั้นวัตถุประสงค์ของงานวิจัยนี้คือเพื่อศึกษาฤทธิ์ต้านเอนไซม์อะเซทิลโคลีนเอสเตอเรสและต้านอนุมูลอิสระของพืชสมุนไพร 13 ชนิด จำนวน 20 ตัวอย่าง ในวงศ์ Asteraceae และ Cucurbitaceae ผลการศึกษาพบว่าสารสกัดจากต้นและใบสาบแมวซึ่งอยู่ในวงศ์ Asteraceae มีฤทธิ์ต้านเอนไซม์อะเซทิลโคลีนเอสเตอเรสที่ดีมาก โดยที่ความเข้มข้น 100 ไมโครกรัม/มิลลิลิตร มีฤทธิ์ต้านเอนไซม์ได้ร้อยละ 78.50 และ 59.48 ตามลำดับ ในการศึกษาฤทธิ์ต้านอนุมูลอิสระ พบว่าสารสกัดจากใบและต้นกระดุมหยกมีฤทธิ์ดีที่สุด มีค่า EC50 เท่ากับ 5.96 และ 6.10 ไมโครกรัม/มิลลิลิตร ตามลำดับ ผลการวิจัยนี้แสดงให้เห็นคุณประโยชน์ของต้นสาบแมว และต้นกระดุมหยก ว่ามีฤทธิ์ต้านเอนไซม์อะเซทิลโคลินเอสเตอเรสและต้านอนุมูลอิสระ สามารถใช้เป็นข้อมูลในการวิจัย เพื่อสกัดสารที่ออกฤทธิ์ ตลอดจนใช้เป็นข้อมูลในการพัฒนาผลิตภัณฑ์อาหารเสริมสำหรับผู้ป่วยอัลไซเมอร์ต่อไป - - - Anti-Acetylcholinesterase and Anti-oxidant Activities of Some Thai Medicinal Plants in Asteraceae and Cucurbitaceae families ABSTRACT Alzheimer’s disease (AD) is neurological disorders which the most prevalent form of dementia and increasing tendency among elderly people. One of several medical treatments of AD is to enhance the neurotransmitter acetylcholine level in the brain using acetylcholinesterase inhibitors (AChEIs). This research aimed to investigate the anti-acetylcholinesterase (AChE) and anti-oxidant activities of 20 extracts of 13 medicinal plants in Asteraceae and Cucurbitaceae families. The results revealed that the stem and leaves extracts of Eupatorium catarium Veldk. in Asteraceae family at the concentration of 100 µg/mL exhibited the most potent anti-AChE activity with the percentage values of 78.50 and 59.48, respectively. The study on anti-oxidant property, the extract of Centratherum punctatum Cass. possessed the strongest activity, leaf and stem extracts showed an EC50 value of 5.96 and 6.10 µg/mL, respectively. The results from this research represent the benefit of Eupatorium catarium Veldk. and Centratherum punctatum Cass. that exhibited anti-acetylcholinesterase and anti-oxidant activities, and will be useful for further research for anti-AChE compounds including for developing dietary supplement for Alzheimer’s pateints.